Prognostic Importance of Early Worsening Renal Function After Initiation of Angiotensin-Converting Enzyme Inhibitor Therapy in Patients With Cardiac Dysfunction - Testani, Jeffrey M.; Kimmel, Stephen E.; Dries, Daniel L.; Coca, Steven G. (Circulation. Heart failure, 2011)
Worsening renal function (WRF) in the setting of heart failure has been associated with increased mortality. However, it is unclear if this decreased survival is a direct result of the reduction in glomerular filtration rate (GFR) or if the mechanism underlying the deterioration in GFR is driving prognosis. Given that WRF in the setting of angiotensin-converting enzyme inhibitor (ACE-I) initiation is likely mechanistically distinct from spontaneously occurring WRF, we investigated the relative early WRF-associated mortality rates in subjects randomized to ACE-I or placebo. Subjects in the Studies Of Left Ventricular Dysfunction (SOLVD) limited data set (n=6337) were studied. The interaction between early WRF (decrease in estimated GFR ≥20% at 14 days), randomization to enalapril, and mortality was the primary end point. In the overall population, early WRF was associated with increased mortality (adjusted hazard ratio [HR], 1.2; 95% CI, 1.0-1.4; P=0.037). When analysis was restricted to the placebo group, this association strengthened (adjusted HR, 1.4; 95% CI, 1.1-1.8; P=0.004). However, in the enalapril group, early WRF had no adverse prognostic significance (adjusted HR, 1.0; 95% CI, 0.8-1.3; P=1.0; P=0.09 for the interaction). In patients who continued to receive study drug despite early WRF, a survival advantage remained with enalapril therapy (adjusted HR, 0.66; 95% CI, 0.5-0.9; P=0.018). These data support the notion that the mechanism underlying WRF is important in determining its prognostic significance. Specifically, early WRF in the setting of ACE-I initiation appears to represent a benign event that is not associated with a loss of benefit from continued ACE-I therapy.